Evaluation of Different Fungicides for the Management of Stem Rust (Puccinia graminis Pers. tritici Erikss. & Henn.) of Wheat - , Keya Chaudhari, Rakeshkumar Jaiman, Ronak Thakkar (Archives of Current Research International, 2024)
Wheat (Triticum aestivum L.) is the most important cereal crop. It belongs to genus Triticum of the family Poaceae. The most prevalent pathogens on wheat are the three rusts viz., black/stem rust (Puccinia graminis Pers. tritici Erikss. and Henn.), leaf/brown rust (Puccinia recondita Rob. Ex. Desm. f. sp. tritici) and yellow/stripe rust (Puccinia striiformis West), which pose serious threat on its production. The present investigations were carried out at Department of Plant Pathology, C. P. College of Agriculture, and Agronomy Instructional Farm, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat during Rabi 2021-22 and 2022-23. The minimum disease severity (21.60 & 22.34%) was recorded in propiconazole 25 EC with maximum (49.01 & 47.28%) disease reduction over control followed by tebuconazole 50% + trifloxystrobin 25% WG during 2021-22 and 2022-23, respectively. The maximum 2727 kg/ha grain yield and 3135 kg/ha straw yield were obtained from the plots treated with propiconazole 25 EC which was followed by tebuconazole 50% + trifloxystrobin 25% WG (2434 kg/ha & 2776 kg/ha), respectively.